2009
DOI: 10.3354/meps08125
|View full text |Cite
|
Sign up to set email alerts
|

Effect of environmental variability and spawner characteristics on the recruitment of Baltic herring Clupea harengus populations

Abstract: We analyzed recruitment -environment relationships for 5 distinct Baltic Sea herring stocks inhabiting the areas of the Western Baltic (WBH), the Main Basin (MBH), the Gulf of Riga (GRH), the Bothnian Sea (BSH) and the Bothnian Bay (BBH). A number of hydro-climatic and biological predictors were tested for their effect on recruitment. Temperature was determined to be an important predictor for 3 of the stocks (MBH, GRH and BSH). However, spawning stock biomass was the major factor explaining recruitment for GR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 50 publications
(47 reference statements)
3
44
0
1
Order By: Relevance
“…The drop in WAA and condition of the spawners could have indirectly contributed to the general decrease in the herring stock, by hampering the population recruitment success (Cardinale et al 2009), likely through reduced fecundity and hatching success of the eggs (Laine & Rajasilta 1999). The decrease in herring body growth also directly contributes to explain the sharper decrease in herring spawning stock biomass, than in stock abundance, since the early 1980s (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The drop in WAA and condition of the spawners could have indirectly contributed to the general decrease in the herring stock, by hampering the population recruitment success (Cardinale et al 2009), likely through reduced fecundity and hatching success of the eggs (Laine & Rajasilta 1999). The decrease in herring body growth also directly contributes to explain the sharper decrease in herring spawning stock biomass, than in stock abundance, since the early 1980s (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…at age 3+). At age 3+, central Baltic herring are fully reproductive (ICES 2009a) and therefore their mean body weight may have an effect on the stock recruitment success (Cardinale et al 2009). Fish older than 5 yr were excluded since in some years they were scarcely represented in our samples (<10 ind.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, the net effect of temperature changes may be different, even opposite, according to the status of main prey, competitor, or predator populations. This has recently been examined in several Northeast Atlantic ecosystems, notably the Baltic (Cardinale et al 2009, Lindegren et al 2010, the Barents Sea (Svendsen et al 2007, Stige et al 2010, and the North Sea (Kempf et al 2010).…”
Section: The Stock-recruitment Relationship Is Enhanced By Including mentioning
confidence: 99%
“…Latest studies into the Central Baltic Sea herring recruitment-environment relationship [2] revealed as important stock recruitment predictors the temperature and the stock weight-at-age of the spawners. Moreover, the food supply is also considered as a significant predictor, suggesting that changes in climate and/or food web structure may indirectly affect herring recruitment via prey availability for the recruits or spawners.…”
Section: Effect Of Environmental Trendsmentioning
confidence: 99%
“…There is a number of studies published on the Central Baltic Sea herring recruitment-environment relationship [2,3] and on substantial decrease in growth rate of the herring that has been observed since the beginning of the 1980s [4][5][6]. It is reported [7] that the decline in the Central Baltic Sea herring spawning stock biomass was partly caused by the reduction in mean weights-atage.…”
Section: Introductionmentioning
confidence: 99%